Transcriptome analysis of the spalax hypoxia survival response includes suppression of apoptosis and tight control of angiogenesis - Malik, Assaf (BioMed Central, 2012)
BACKGROUND: The development of complex responses to hypoxia has played a key role in the evolution of mammals, as inadequate response to this condition is frequently associated with cardiovascular diseases, developmental disorders, and cancers. Though numerous studies have used mice and rats in order to explore mechanisms that contribute to hypoxia tolerance, these studies are limited due to the high sensitivity of most rodents to severe hypoxia. The blind subterranean mole rat Spalax is a hypoxia tolerant rodent, which exhibits unique longevity and therefore has invaluable potential in hypoxia and cancer research. RESULTS: Using microarrays, transcript abundance was measured in brain and muscle tissues from Spalax and rat individuals exposed to acute and chronic hypoxia for varying durations. We found that Spalax global gene expression response to hypoxia differs from that of rat and is characterized by the activation of functional groups of genes that have not been strongly associated with the response to hypoxia in hypoxia sensitive mammals. Using functional enrichment analysis of Spalax hypoxia induced genes we found highly significant overrepresentation of groups of genes involved in anti apoptosis, cancer, embryonic/sexual development, epidermal growth factor receptor binding, coordinated suppression and activation of distinct groups of transcription factors and membrane receptors, in addition to angiogenic related processes. We also detected hypoxia induced increases of different critical Spalax hub gene transcripts, including antiangiogenic genes associated with cancer tolerance in Down syndrome human individuals. CONCLUSIONS: This is the most comprehensive study of Spalax large scale gene expression response to hypoxia to date, and the first to use custom Spalax microarrays. Our work presents novel patterns that may underlie mechanisms with critical importance to the evolution of hypoxia tolerance, with special relevance to medical research.